BENTUK DAN MAKNA ENDE JEIR PADA MASYARAKAT MANDAILING DI KELURAHAN WEK V PADANGSIDIMPUAN - LAURI NOVITA SINAGA (Universitas Negeri Medan, 2018)
Lauri Novita Sinaga. NIM 2131140024. Forms And Meaning Of Ende Jeir In The Mandailing Society InWek V Village Padangsidimpuan. Faculty of Language and Art. State University of Medan 2017.This study aims to determine the form and significance of the Ende Jeir in the Mandailing Society inKelurahan Wek V Padangsidimpuan. The purpose of this research is to find out the form of Ende Jeirsong in Mandailing community in Wek V Padangsidimpuan Village, to know the meaning contained inEnde Jeir in Mandailing community in Wek V Padangsidimpuan Village, to know the function of EndeJeir in Mandailing community in Wek V Village Padangsidimpuan, to know the response of local peopleto preserve Ende Jeir on Mandailing community in Wek V Padangsidimpuan Village.The theory used is form, meaning, function, and Ende. The shape is the arrangement of the frame of asong that is determined according to the parts of the sentence. Meaning is the purpose that is derivedfrom things that want to be shown by something or want to be expressed, exposed, with the word actuallydoes not interfere with the value of taste. The function of music is to express the taste, and simultaneouslyas an activity of various types of human communication. Ende is a traditional song (folksong), whichrepresents the representation of structure, function and cultural values.Methods in this research using qualitative descriptive method. The samples in this study were the lectureand audio visuals of Ende Jeir, singer Ende Jeir, artist and community Wek V Padangsidimpuan Village.This data collection is done by observation method or observation, interview, and documentation. Thisresearch was taken at Kelurahan Wek V Padangsidimpuan, and this research was conducted from August2017.The results of this study indicate that the form of Ende Jeir song consists of a one part song form, with AA 'form. the meaning of Ende Jeir is a prayer, plea, expectation of parents to his daughter who is doingthis marriage and singing to advise on a good domestic life. Ende Jeir function is as symbolicrepresentation media, media of emotional expression and media of cultural preservation. Ende Jeir needsto be preserved because it begins to be forgotten and left behind. For that, it needs to be developed andintroduced in the young generation so as not to just disappear.